Politeness Used by Islamic Education Department Administration Staff of State Islamic University North Sumatra. Postgraduate School of the State University of Medan - Akhrif Yahsya (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
The objectives of this study is to find out what and how the using of politeness strategies used by Islamic Education Department Administration Staff and why they use it when interact with the students by using Brown and Levinson theory. This research is qualitative study. The data is gathered from administration staff who work in Islamic Education Department of State Islamic University North Sumatra. To get the data the researcher used sound recorder to find out the use of politeness strategies. From the analysis, the researcher found that there are four politeness strategies used by administration staff when they interact to the students. They are greeting, question, command, and request. The most of strategies used in the field are bald on record rather than positive and negative politeness strategy. They used these strategies to save the time, because there are so many students have to be served. The other reason is diversity age and avoiding the ambiguity. The staff sometimes uses positive and negative politeness strategies. They used positive politeness especially for recognized students to make closeness and friendly when they ask them to do something and they used negative politeness strategies to save face student awareness when the staff tried to judge students by doing mistake. The implication of this study is to increase the using of positive politeness strategies when administration staff talk to the students. This is because the positive politeness strategies can minimize Face Threatening Acts to endeavor a harmony in social interaction.